Study of the coupling effect of CO2 and PM2.5 emissions: A case study of yangtze river delta, China - Wengin Chung; Chao Liu (Heliyon)
Many countries are confronted with the dual challenge of mitigating CO2 emissions and controlling PM2.5 pollution, attributed to the impacts of global climate change. This study explores the spatio-temporal pattern of the coupling effect between CO2 emissions and PM2.5 pollution by conducting a case study of the Yangtze River Delta (YRD) region of China and aims to identify the urban influencing factors that contribute to this coupling effect. Utilizing a coupled coordination model, this study conducted a spatio-temporal analysis of CO2 emissions and PM2.5 concentrations from 2008 to 2020.The model assessed the year-by-year coupling coordination degrees of CO2 and PM2.5 emissions in each of the five provinces in the YRD region.This study's three main findings are the following: (1) The overall coupling coordination between CO2 and PM2.5 emissions exhibited a declining trend from 2013 to 2017, followed by a rebound in 2018. Most cities experienced their highest degree of coupling in 2020. (2) Of 41 cities in the YRD region, only 10 have achieved a state of coordinated development. This finding suggests that approximately 24 % of the YRD region attained a positive degree of coordination. (3) The megacity Shanghai has achieved a stage characterized by high-quality coordination, emphasizing the city's significant role in mitigating CO2 emissions and managing PM2.5 pollution in the region. In addition, the analysis of urban influencing factors revealed a significant correlation between several key urban factors, including land area, green space and water area, road network, technical development, and industrial structure.This study recommends that cities aiming to reduce CO2 emissions and control PM2.5 pollution consider initiatives that address the coupling effect, such as optimizing industrial land use and prioritizing spatial planning strategies. The selection of the YRD region as the study area provides an exemplary model that offers implications not only for other regions in China but also for other countries that face similar issues.